Substrate dependence of the mechanism of EcoRI endonuclease. - Rubin, R A (1978)
The mechanism of EcoRI endonuclease is substrate dependent. At 37 degrees dissociation of the enzyme-Form II DNA intermediates of ColE1 DNA and bacteriophage G4 RFI DNA is negligible. Therefore, both DNA strands with in the EcoRI sequence are cleaved during a single binding event. However, double strand cleavage of SV40 DNA occurs without dissociation of the enzyme in only 75% of the catalytic events. This mechanistic difference presumably reflects sequence differences about the EcoRI sites of these DNA's.